Rethinking primary care visits: how much can be eliminated, delegated or performed outside of the face‐to‐face visit?. Issue 4 (10th March 2015) - Pelak, Mary; Pettit, Amy R.; Terwiesch, Christian; Gutierrez, Jennifer C.; Marcus, Steven C.
Abstract Rationale, aims and objectives Office visits represent the core component of primary care practice, but little is known about what percentage of primary care provider (PCP) visit time could be suitable for reassignment to another medical home team member or to a non‐face‐to‐face modality (e.g. secure messaging) in order to optimize face‐to‐face PCP visit time. Method We videotaped 121 PCP office visits at four Veterans Health Administration Medical Centers and divided visits into discrete activity segments. Two physicians reviewed each visit recording and provided independent clinical judgments regarding which segments might be suitable for reassignment. We examined the activity category distribution of visit time rated as needing face‐to‐face time with a PCP. Results Reviewers judged 53% of the 5398 minutes of rated visit time as suitable for reassignment to another team member or modality. The percentage of time rated as needing face‐to‐face PCP care varied greatly by activity category, from a high of 73.9% (for examining patients) to a low of 16.2% (for medication review). Rater agreement regarding tasks' suitability for reassignment varied across activity categories. Conclusions These data offer an example of how face‐to‐face PCP visit time might be optimized as practices seek to shift components of patient care to other team members and other modalities. Given variations in provider preferences and judgments, successful redesign efforts will need to involve stakeholders in decisions about how to best utilize medical home resources.